Expert-approved best practice recommendations on the use of sedative drugs and intentional sedation in specialist palliative care (SedPall) - Ostgathe, Christoph; Bausewein, Claudia; Schildmann, Eva; Bazata, Jeremias; Handtke, Violet; Heckel, Maria; Klein, Carsten; Kremling, Alexander; Kurkowski, Sandra; Meesters, Sophie; Seifert, Andreas; Torres Cavazos, Jorge; et al. (BMC Palliative Care, 2023)
Background: The use of sedative drugs and intentional sedation in end-of-life care is associated with clinical, ethical and legal challenges. In view of these and of the issue’s great importance to patients undergoing intolerable suffering, we conducted a project titled SedPall (“From anxiolysis to deep continuous sedation – Development of recommendations for sedation in palliative care“) with the purpose of developing best practice recommendations on the use of sedative drugs and intentional sedation in specialist palliative care and obtaining feedback and approval from experts in this area. Design: Our stepwise approach entailed drafting the recommendations, obtaining expert feedback, conducting a single-round Delphi study, and convening a consensus conference. As an interdisciplinary group, we created a set of best practice recommendations based on previously published guidance and empirical and normative analysis, and drawing on feedback from experts, including patient representatives and of public involvement participants. We set the required agreement rate for approval at the single-round Delphi and the consensus conference at ≥80%. Results: Ten experts commented on the recommendations’ first draft. The Delphi panel comprised 50 experts and patient and public involvement participants, while 46 participants attended the consensus conference. In total, the participants in these stages of the process approved 66 recommendations, covering the topics “indications”, “intent/purpose [of sedation]”, “decision-making”, “information and consent”, “medication and type of sedation”, “monitoring”, “management of fluids and nutrition”, “continuing other measures”, “support for relatives”, and “team support”. The recommendations include suggestions on terminology and comments on legal issues. Conclusion: Further research will be required for evaluating the feasibility of the recommendations’ implementation and their effectiveness. The recommendations and the suggested terminology may serve as a resource for healthcare professionals in Germany on the use of sedative drugs and intentional sedation in specialist palliative care and may contribute to discussion on the topic at an international level. Trial Registration: DRKS00015047 (German Clinical Trials Register)
CRIS-Team Scopus Importer:2023-09-15
Keywords: Community-based participatory research; Empirical research; Hypnotics and sedatives; Palliative care; Practice guidelines; Terminal care